Dampak Tax Planning dan Digitalisasi Layanan Pajak terhadap Kepatuhan Wajib Pajak dimoderasi oleh Nasionalisme - Sihar Tambun; Resti Riandini (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study was to examine tax planning, digitization of tax services, and nationalism on taxpayer compliance. As well as testing the moderating effect of tax planning and digitization of tax services on taxpayer compliance. The research method used is a quantitative method with data collection techniques, namely through a questionnaire with a random sampling method, the sampling method using the hair method, namely the number of respondents 5-10 times the number of indicators. The number of samples obtained is as many as 299 respondents as taxpayer status reported online. The sample was tested for validity and reliability as well as hypothesis testing through the Smart PLS software application. The results of the hypothesis test prove that there is no significant effect of tax planning on taxpayer compliance, there is a significant effect of digitizing services on taxpayer compliance, there is a significant effect of nationalism on taxpayer compliance, and there is no significant effect of moderating nationalism. on the effect of tax planning on taxpayer compliance, as well as the significant influence of nationalism moderation on the effect of digitizing services on taxpayer compliance. From this research, it can be said that when the government improves taxpayer compliance, it is necessary to improve, namely nationalism, service digitization, and moderation of nationalism on the influence of service digitization. Keywords: Digitization of tax; Nationalism; Taxpayer Compliance; Tax Planning; Tax Service